Analisis Kesiapan Perpustakaan Perguruan Tinggi Indonesia dalam Mengadaptasi Teknologi Metaverse melalui Teknik Delphi - Dian Arya Susanti; Herli Bahtiar Saleh; Yunus Winoto (Media Pustakawan, 2023)
Metaverse is not a new technology, and has also been adapted by several libraries abroad. In Indonesia, many studies are still needed related to metaverse technology adaptation in libraries and the library that is most likely to carry out this adaptation is the higher education library. This is because higher education libraries generally have more qualified resources than other types of libraries. This study aims to see the readiness of Higher Education Libraries in adapting the Metaverse technology which is an analysis of the opinions of sources selected based on their respective competencies (purposive sampling). This study uses the Delphi technique which is part of the forecasting technique, by prioritizing the formation of consensus which is achieved through structured communication that is systematic and interactive. Based on the results of the analysis, twenty-four points were found which became pillars of the readiness of librarians and higher education libraries in adapting metaverse technology, and seven of them became the main pillars, namely ecosystem, collaboration, infrastructure, tools, budget, role models and legal aspects. If all of these seven prerequisite points have been met in Higher Education, then the adaptation of metaverse technology can run well. Recommendations for further research related to the readiness of librarian resources in adapting the metaverse in the university library and how the acceptance of users and the expectations of users in adapting metaverse technology in the library is needed as a follow-up research.